Robot-assisted vs. conventional MIDCAB: A propensity-matched analysis - Gofus, Jan; Cerny, Stepan; Shahin, Youssef; Sorm, Zdenek; Vobornik, Martin; Smolak, Petr; Sethi, Ananya; Marcinov, Samuel; Karalko, Mikita; Chek, James; Harrer, Jan; Vojacek, Jan; et al. (Frontiers in cardiovascular medicine, 2022)
BACKGROUND: Robotic assistance (RA) in the harvesting of internal thoracic artery during minimally invasive direct coronary artery bypass grafting (MIDCAB) provides several potential benefits for surgeon and patient in comparison with conventional MIDCAB. The two technical options have not been thoroughly compared in the literature yet. We aimed to perform this in our cohort with the use of propensity-score matching (PSM). METHODS: This was a retrospective comparison of all consecutive patients undergoing conventional MIDCAB (2005-2021) and RA-MIDCAB (2018-2021) at our institution with the use of PSM with 27 preoperative covariates. RESULTS: Throughout the study period 603 patients underwent conventional and 132 patients underwent RA-MIDCAB. One hundred and thirty matched pairs were selected for further comparison. PSM successfully eliminated all preoperative differences. Patients after RA-MIDCAB had lower 24 h blood loss post-operatively (300 vs. 450 ml, p = 0.002). They had shorter artificial ventilation time (6 vs. 7 h, p = 0.018) and hospital stay (6 vs. 8 days, p < 0.001). There was no difference in the risk of perioperative complications, short-term and mid-term mortality between the groups. CONCLUSIONS: RA-MIDCAB is an attractive alternative to conventional MIDCAB. It is associated with lower post-operative blood loss and potentially faster rehabilitation after surgery. The mortality and the risk of perioperative complications are comparable among the groups.
Keywords: internal thoracic artery; MIDCAB; coronary artery bypass grafting; minimally invasive surgery; robotic surgery